Socioeconomic Inequalities in Oral Health-Related Quality of Life among Brazilians: A Cross-Sectional Study - Fabíola Bof de Andrade; Flavia Cristina Drumond Andrade (MDPI AG, 2019)
Objective: Assess the magnitude of the socioeconomic inequalities related to the impact of oral health on quality of life among adults and elderly individuals. Methods: This was a cross-sectional study with data from the most recent oral health survey from the state of Minas Gerais, Brazil. The sample included data on 2288 individuals—1159 adults in the 35–44 age group and 1129 adults in the 65–74 age group. Socioeconomic inequalities in Oral Impacts on Daily Performance ratings were measured using two inequality measures: the slope index of inequality (SII) and the relative index of inequality (RII). Results: The prevalence of negative impact of oral health on quality of life was 42.2% for the total sample, 44.9% among adults and 37.5% among elderly individuals. Significant absolute and relative income inequalities were found for the total sample (SII −27.8; RII 0.52) and both age groups (adults: SII −32.4; RII 0.49; elderly: SII −18.3; RI 0.63), meaning that individuals in the lowest income level had the highest prevalence of negative impacts. Regarding schooling, no significant differences were observed among the elderly. Conclusion: There were significant socioeconomic inequalities related to the negative impact of oral health-related quality of life in Brazil among both age groups.